Решить систему неравенств: 23(х+1)> x^2 23(x+2)> x^2

zavirohinoleksa zavirohinoleksa    1   29.07.2019 10:50    0

Ответы
kulaevmasya kulaevmasya  03.10.2020 16:30
23x+23>x^2
x^2-23x-23<0
x^2-23x-23=0
D=b^2-4ac
D=529+92=621
x₁=\frac{23- 3\sqrt{69} }{2}     x₂=\frac{23+3 \sqrt{69} }{2}

......+..........\frac{23- 3\sqrt{69} }{2} .........-............\frac{23+3 \sqrt{69} }{2}..........+......
x∈(\frac{23- 3\sqrt{69} }{2} ;\frac{23+3 \sqrt{69} }{2})
23x+46>x^2
x^-23x-46<0
D=b^2-4ac
D=529+196=713
x₁=\frac{23- \sqrt{713} }{2}     x₂=\frac{23+\sqrt{713} }{2}
x∈(\frac{23- \sqrt{713} }{2} ;\frac{23+\sqrt{713} }{2})
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика